(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
In addition to the studys main focus on smartphone addiction among Sultan Qaboos University Undergraduates undergraduates, it also investigated particular issues such as the following: smartphone applications and activities that students were most addicted to, the impact of addiction on academic achievement, and addiction variation according to gender, field of study, parental education and family income. A ques tionnaire was distributed to a random sample of 140 undergraduates (37.1% males and 62.9% females) Findings revealed that what the study calls a casual level of addiction (42.3%) was the most common, followed by a heavy level (30.8%), and finally a moderate level (26.%). While messaging was the activity students were most addicted to, no significant differences were found that related to academic achievement. Males were more addicted than females, but nothing significant emerged in relation to field of study, parental education and family income.